2020
DOI: 10.1007/s10008-019-04489-x
|View full text |Cite
|
Sign up to set email alerts
|

Penta-coordinated transition metal macrocycles as electrocatalysts for the oxygen reduction reaction

Abstract: The oxygen reduction reaction (ORR) is a highly important reaction in electrochemistry. The following short review details recent advances in novel non-precious metal catalysts containing transition metal macrocycles for use in the ORR. Unbound, many of these electrodes were found to generate high levels of side products such as O 2 − and H 2 O 2 via 2-electron processes, and for this reason, it is aimed to create systems which would favor a 4-electron process which would completely convert oxygen to H 2 O. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 144 publications
1
14
0
Order By: Relevance
“…This also relates with the differences in the M–N bond length in the catalyst structure after pyrolysis. Finally, if we consider the catalytic activity as log j k at constant potential ( E : 0.8 V vs. RHE) versus binding energy M-O 2 and also versus the formal potential, as proposed by several authors 10 , 16 , 61 , 97 99 , we obtain the figure reported as graphical abstract, where the MN4 structure is maintained, and the catalysts follow the trend of the correlations.…”
Section: Introductionmentioning
confidence: 98%
“…This also relates with the differences in the M–N bond length in the catalyst structure after pyrolysis. Finally, if we consider the catalytic activity as log j k at constant potential ( E : 0.8 V vs. RHE) versus binding energy M-O 2 and also versus the formal potential, as proposed by several authors 10 , 16 , 61 , 97 99 , we obtain the figure reported as graphical abstract, where the MN4 structure is maintained, and the catalysts follow the trend of the correlations.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, Tasca et al. ( Cao et al., 2013 ; Riquelme et al., 2018 ; Viera et al., 2020 ; Loyola et al., 2021a , 2021b ; Govan et al., 2021 ; Oyarzun et al., 2021 ) systematically studied similar Fe-centered and Co-centered complexes with axial ligands by combining experiments and theoretical calculation. They also demonstrated that the additional coordination promotes the overall ORR performance.…”
Section: Resultsmentioning
confidence: 99%
“…Since cobalt phthalocyanine (CoPc) was first used in fuel cells in 1964, many N 4 ‐chelated MMC have been studied as excellent alternatives to Pt‐based ORR catalysts in fuel cells and metal–air batteries. [ 38–46 ] Such complexes are comprised of different central metal ions and macrocyclic ligands exhibiting flexible and adjustable substituents and forming a unique M N 4 structure. Furthermore, the square planar geometry of the central metal ion is conducive to the binding and activation of ORR‐related intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, O 2 molecules can axially combine with metal ions and are transformed stepwise into different reaction intermediates through the transfer of electrons and protons. [ 39,47,48 ]…”
Section: Introductionmentioning
confidence: 99%